PENGARUH BEAUTY VLOGGER DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MELALUI MEDIA SOSIAL DALAM PERSFEKTIF EKONOMI ISLAM - Fadillah Fadillah; Lucky Enggrani Fitri; Paulina Lubis (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research aims to determine the effect of Beauty Vloggers and Celebrity Endorsers on purchasing decisions through social media from the perspective of Islamic Economics. This research method was carried out with a quantitative approach and an associative research design. The primary data used was obtained through the distribution of questionnaires and processed using SPSS 26. The data will then be analyzed using multiple linear regression. The results of this study show that: (1) Beauty vlogger and Celebrity Endorser partially have a positive and significant influence on purchasing decisions; (2) Beauty vloggers and Celebrity Endorsers simultaneously have a positive and significant effect on purchasing decisions (3) Beauty vloggers or celebrity endorsers have criteria in make-up, namely that apart from being halal, it must be thayyib (good) and also according to the portion (not excessive). Then, in promoting an item that must be possessed, namely the nature of trustworthiness, honest communicativeness and intelligence. similar to what the Prophet Muhammad SAW did in carrying out trading activities.